Polymer electrolyte containing oxygen vacancy vanadium-based filler and preparation method and application thereof

By preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler, the problems of high raw material cost and complex preparation process in all-solid-state metal batteries have been solved, realizing efficient and environmentally friendly electrolyte preparation, improving the ion conduction performance and battery life of the battery, and adapting it to the industrialization of high-energy-density all-solid-state sodium metal batteries.

CN120955209AActive Publication Date: 2025-11-14INNER MONGOLIA UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511478245.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2025-11-14
Estimated Expiration
2045-10-16

AI Technical Summary

Technical Problem

Existing polymer electrolytes for all-solid-state metal batteries suffer from high raw material costs, complex preparation processes, and severe environmental pollution. They also have insufficient ionic conductivity and sodium ion transport performance, which limits their industrial application in high-energy-density and high-safety all-solid-state sodium metal batteries.

Method used

The polymer electrolyte uses vanadium-based filler containing oxygen vacancies. The oxygen vacancies filler is prepared by calcining vanadium pentoxide at low temperature. The polymer electrolyte membrane is prepared by combining conventional chemicals such as succinic acid, ethoxylated trimethylolpropoxide and fluoroethylene carbonate with ultraviolet light curing technology, thus avoiding the use of toxic solvents and realizing continuous production.

Benefits of technology

It reduces raw material costs, simplifies the preparation process, improves room temperature ionic conductivity and sodium ion transport efficiency, widens the voltage window, enhances battery charge and discharge efficiency and long-cycle stability, adapts to high-current discharge, and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120955209A_ABST
    Figure CN120955209A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer electrolyte containing oxygen vacancy vanadium-based filler and a preparation method and application thereof, and relates to the technical field of battery materials, and the preparation method comprises the following steps: (1) preparing a deep eutectic solution; (2) mixing; (3) preparing a precursor solution; and (4) preparing the polymer electrolyte membrane. The polymer electrolyte is prepared by the preparation method. The polymer electrolyte is applied to a solid-state sodium metal battery. The preparation method of the polymer electrolyte containing the oxygen vacancy vanadium-based filler, disclosed by the invention, has the beneficial effects that the raw material cost is low, the industrial adaptability is high, the process is environment-friendly and efficient, and continuous production can be realized. The polymer electrolyte has a wide voltage window, adapts to a high-voltage positive electrode, has high ion conduction efficiency, adapts to room-temperature application, effectively reduces concentration polarization in the ion transmission process, and improves the charging and discharging efficiency of the battery. The solid-state sodium metal battery has high power potential, adapts to high-current discharge and has long cycle stability, and the service life of the solid-state sodium metal battery is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, specifically to a polymer electrolyte with oxygen-vacancy vanadium-based filler, its preparation method, and its application. Background Technology

[0002] The growing demand for wearable electronic devices has accelerated the development of efficient and flexible energy storage solutions. Among these batteries, all-solid-state sodium metal batteries have extremely high development potential. Their key component is the solid electrolyte, which can be broadly classified into two categories: inorganic solid electrolytes and polymer solid electrolytes. Although inorganic solid electrolytes have excellent ionic conductivity and a wide voltage window, their inherent brittleness, limited thermodynamic stability, sensitivity to moisture, and high-voltage processing requirements hinder their application in flexible devices.

[0003] Ethoxylated trimethylolpropane triacrylate (TMA) has become a valuable polymer electrolyte monomer due to its photocurability, ability to form a stable three-dimensional network, ion conduction promoting ability, and good mechanical properties. It has shown potential in improving battery energy density, cycle life, and safety. However, limited sodium salt dissociation and low Na+ content are limitations. + Transportation issues lead to low reduced ionic conductivity, limiting its widespread application. To address these problems, the main modification methods can be categorized as follows: copolymerization, crosslinking, or the addition of plasticizers, among which the introduction of inorganic fillers is a multifunctional and synergistic strategy for preparing composite polymer electrolytes. It not only significantly improves both ionic conductivity and mechanical strength simultaneously, but also brings unique benefits such as interface stability and enhanced safety, and is considered one of the key technological paths for realizing the industrialization of high-energy-density all-solid-state batteries. Patent application CN202510937319.5 discloses a method for preparing lithium metal batteries based on two-dimensional inorganic filler polymer electrolytes. By preparing polymer electrolytes based on two-dimensional inorganic fillers, the problems of low ionic conductivity and insufficient mechanical strength of polymer electrolytes are solved, achieving high-safety and high-performance lithium metal batteries. However, the following problems still exist: 1. Two-dimensional inorganic fillers (nano-molybdenum disulfide, graphene, Ti3C2T) x 1) These are high-end nanomaterials with high purchase costs and poor industrial adaptability; 2) Using two-dimensional fillers to improve ion conduction relies solely on interlayer confined transport to enhance conduction, failing to address the problem of disordered ion migration, thus resulting in a low upper limit for ion conduction performance; 3) Using solution casting to prepare electrolytes requires dissolving the two-dimensional filler, polymer, and lithium salt in toxic solvents such as N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DMF), followed by evaporation of the solvent at 60~80℃. Therefore, not only does solvent evaporation easily cause environmental pollution (requiring additional waste gas treatment), but solvent residue can also easily lead to a decrease in electrolyte purity.

[0004] In summary, the current field of polymer electrolytes for all-solid-state metal batteries urgently needs to develop a polymer electrolyte based on vanadium-based fillers with low raw material costs, simple and environmentally friendly preparation processes, and controllable performance. Simultaneously, it is necessary to solve core problems such as "low room temperature ionic conductivity and low cation transfer number". In particular, it is necessary to adapt to the transport characteristics of sodium-ion batteries, so as to provide a feasible technical path for the industrialization of high-energy-density and high-safety all-solid-state sodium metal batteries. Summary of the Invention

[0005] In view of this, the purpose of this invention is to provide a polymer electrolyte with oxygen-vacancy vanadium-based filler, its preparation method, and its applications. The preparation method provided by this invention has low raw material costs, strong industrial adaptability, and is environmentally friendly and efficient, enabling continuous production. The polymer electrolyte has a wide voltage window, is suitable for high-voltage cathodes, has high ion conductivity, is suitable for room temperature applications, effectively reduces concentration polarization during ion transport, and improves battery charge and discharge efficiency. Solid-state sodium metal batteries have high power potential, are suitable for high-current discharge, have long cycle stability, and significantly extended lifespan.

[0006] The present invention discloses a method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler, which includes the following steps: (1) Preparation of deep eutectic solution: Succinate (SN) and sodium salt are mixed evenly at a mass ratio of 2-2.5:1 to obtain a clear and transparent deep eutectic solution; the deep eutectic structure can significantly improve the dissociation efficiency of sodium salt, laying the foundation for subsequent ion conduction.

[0007] (2) Mixing: The deep eutectic solution in step (1) is mixed with ethoxylated trimethylolpropane triacrylate (ETPTA) and fluoroethylene carbonate (FEC) in a mass ratio of 1:0.3-0.5:0.05-0.1 to obtain a mixture; wherein, ETPTA is a photocurable polymer monomer that can form a three-dimensional network structure to ensure the mechanical strength of the electrolyte; FEC is a plasticizer that can reduce the crystallinity of the polymer and accelerate Na⁺ transport.

[0008] (3) Preparation of precursor solution: The mixture in step (2) is mixed with vanadium-based inorganic filler at a mass ratio of 1:0.05-0.1 to form a precursor solution; wherein the oxygen vacancies in the vanadium-based inorganic filler can anchor the anions generated by the dissociation of sodium salt and promote the dissociation of Na+. + Directed transmission. (4) Preparation of polymer electrolyte membrane: The precursor solution and initiator in step (3) are mixed evenly at a mass ratio of 1:0.005-0.01, and then dropped onto the glass fiber membrane to completely wet the glass fiber membrane. Then, the membrane is irradiated with an ultraviolet lamp for 10-30 min to induce photopolymerization of ETPTA and obtain the polymer electrolyte membrane.

[0009] Furthermore, the sodium salt in step (1) is sodium bis(trifluoromethanesulfonyl)imide.

[0010] Furthermore, the preparation method of the vanadium-based inorganic filler in step (3) includes the following steps: placing vanadium pentoxide powder in a reducing gas and calcining it at a temperature of 350-400℃ for 1-2 hours to obtain vanadium-based inorganic filler containing oxygen vacancies.

[0011] The specific reaction formula is as follows:

[0012] In the hydrogen-argon mixture, argon isolates the V2O5 from air to prevent re-oxidation; the temperature of 350~400℃ provides kinetic energy for hydrogen (H2), causing it to adsorb onto the surface / defect sites of V2O5, and then dissociate into reducing hydrogen protons (H). + Vanadium pentoxide provides active species for the reduction reaction with free electrons (e⁻). Vanadium in vanadium pentoxide is reduced from a high valence state to a low valence state, resulting in a decrease in the positive charge of vanadium and a partial charge imbalance (positive charge deficiency) in the crystal lattice. To maintain electroneutrality, the negative charge needs to be eliminated through oxygen atom desorption; that is, the charge imbalance drives the oxygen ions (O⁻) in the crystal lattice to dissipate. 2- ) and H + The reaction produces water molecules (H2O), which desorb in a gaseous state; O 2- The detached lattice sites form oxygen vacancies, which are mainly distributed on the surface / near surface of V2O5, in the form of single vacancies / double vacancies (non-aggregated state); at 350~400℃, which is below the melting point of V2O5 (690℃), only the surface / near surface is reduced, and the main [VO5] structure is not destroyed, providing support for oxygen vacancies.

[0013] Furthermore, the reducing gas is a hydrogen-argon mixture, wherein hydrogen accounts for 3-5% of the mass of the hydrogen-argon mixture.

[0014] Furthermore, the initiator in step (4) is 2-hydroxy-2-methylacetone.

[0015] Furthermore, steps (1)-(4) are carried out under an argon protective atmosphere.

[0016] On the other hand, a polymer electrolyte containing oxygen-vacancy vanadium-based filler is disclosed, which is prepared into a polymer electrolyte membrane using the above-mentioned preparation method.

[0017] Furthermore, the polymer electrolyte membrane has a thickness of 800-980 μm, balancing ion conduction efficiency and mechanical support performance.

[0018] On the other hand, the application of polymer electrolytes with oxygen-vacancy vanadium-based fillers in solid-state sodium metal batteries was disclosed.

[0019] Advantages of this invention: 1. This invention discloses a method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler. The filler used in this invention is conventional vanadium pentoxide that has undergone reduction treatment, not high-end nanomaterials (such as graphene, Ti3C2T). x The procurement cost is significantly reduced; other raw materials (butadienenitrile, fluoroethylene carbonate, and ethoxylated trimethylolpropane triacrylate) are all commonly used chemicals in the battery field, which are easy to obtain and have stable prices, avoiding dependence on scarce or expensive raw materials, thus resulting in low raw material costs and strong industrial adaptability.

[0020] 2. This invention discloses a method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler. The process is environmentally friendly and efficient, requiring no use of toxic organic solvents such as NMP and DMF, thus avoiding environmental pollution caused by solvent volatilization (no additional waste gas treatment is needed), and eliminating the problem of electrolyte purity reduction caused by solvent residue. Moreover, by adjusting the calcination temperature (350~400℃) and time (1~2h) of V2O5, the oxygen vacancy concentration can be precisely controlled, avoiding structural collapse due to excessive vacancies and insufficient performance due to insufficient vacancies. The polymer is cured by ultraviolet light irradiation for 10~30min, and the photocuring efficiency is much higher than that of traditional thermal curing, enabling continuous production.

[0021] 3. This invention discloses a polymer electrolyte with oxygen-vacancy vanadium-based filler, featuring a wide voltage window suitable for high-voltage cathodes (maximum voltage window up to 5.5V, significantly higher than unfilled electrolytes). It can be matched with high-voltage materials such as sodium vanadium phosphate and nickel-based sodium-rich cathodes, significantly broadening the selection range of battery cathode materials and laying the foundation for high-energy-density batteries. It also boasts high ion conductivity, suitable for room-temperature applications (room-temperature ion conductivity reaches 2.98 mS / cm and 3.13 mS / cm, significantly higher than unfilled electrolytes), accelerating Na+ ionization. + The transport of sodium ions reaches 0.322, which effectively reduces concentration polarization during ion transport and improves battery charging and discharging efficiency.

[0022] 4. This invention discloses the application of a polymer electrolyte with oxygen-vacancy vanadium-based filler in a solid-state sodium metal battery, wherein the solid-state sodium metal battery has high power potential and is suitable for high-current discharge; that is, the critical current density of this invention reaches 2.6 mA / cm². 2 It has twice the capacity of fillerless solid sodium metal batteries, can withstand higher charge and discharge currents, and meets the high power requirements of wearable devices, portable energy storage and other scenarios. It has long cycle stability and significantly extended lifespan. That is, after 200 cycles at 0.5C rate, the capacity retention rate of the battery of this invention is as high as 98% or more, and the polarization voltage is stable. In contrast, the capacity of fillerless solid sodium metal batteries begins to decay significantly after 100 cycles, and the retention rate after 200 cycles is less than 80%. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is the X-ray diffraction pattern of the vanadium-based inorganic filler in Example 1 of the present invention.

[0025] Figure 2 This is the X-ray diffraction pattern of the polymer electrolyte membrane in Example 1 of the present invention.

[0026] Figure 3 This is a comparison diagram of the voltage windows of solid sodium metal batteries in Examples 4-7 and Comparative Example 1 of the present invention.

[0027] Figure 4 The images show the electrochemical impedance spectroscopy of solid sodium metal batteries from Examples 4-7 and Comparative Example 1 of this invention.

[0028] Figure 5 The chronocurrent curve (It) and impedance diagram before and after polarization are shown for the solid sodium metal battery of Comparative Example 1.

[0029] Figure 6 The chronocurrent curve (It) and impedance diagram before and after polarization of the solid sodium metal battery in Example 4 of this invention are shown.

[0030] Figure 7 This is a comparison curve of the critical current density of solid sodium metal batteries in Example 4 and Comparative Example 1 of the present invention.

[0031] Figure 8 For the solid-state sodium metal battery of Example 4 and Comparative Example 1 of the present invention, at 0.1 mA / cm 2 Voltage-time curves at current density.

[0032] Figure 9 This is a comparison chart of the long-cycle capacity of the solid sodium metal battery of Example 4 and Comparative Example 1 at a rate of 0.5C. Detailed Implementation

[0033] The present invention will be further described in detail below through embodiments.

[0034] Example 1: 1. Preparation of vanadium-based inorganic fillers containing oxygen vacancies Vanadium pentoxide powder was placed in a hydrogen-argon mixture atmosphere with a hydrogen mass ratio of 5%, heated to 350℃, and calcined for 2 hours. After natural cooling, vanadium-based inorganic filler containing oxygen vacancies was obtained. X-ray diffraction (XRD) analysis was performed (see...). Figure 1 The characteristic peaks of this filler are slightly shifted compared to pure V2O5, indicating lattice expansion and proving the introduction of oxygen vacancies.

[0035] 2. Preparation of polymer electrolyte membrane (1) In an argon glove box (ambient temperature 25℃), 1.0g of succinate and 0.4g of sodium bis(trifluoromethanesulfonyl)imide were mixed and stirred at room temperature for 30 minutes to form a clear and transparent deep eutectic solution. (2) Add 0.3g of ethoxylated trimethylolpropane triacrylate and 0.05g of fluoroethylene carbonate to the above deep eutectic solution, stir at room temperature for 2.5 hours to obtain a homogeneous mixture; (3) Add 0.1g of the vanadium-based inorganic filler prepared above to the mixture and stir at room temperature for 1 hour to form a uniformly dispersed precursor solution; (4) Add 0.01 g of 2-hydroxy-2-methylphenylacetone to the precursor solution, stir for 10 minutes to mix evenly, then drop it onto the glass fiber membrane, ensuring the membrane is completely wetted; irradiate with a 365 nm UV lamp for 20 minutes to obtain a polymer electrolyte membrane (approximately 950 μm thick); analyze by XRD (see... Figure 2 The characteristic diffraction peaks of V2O5 can be clearly observed in the XRD pattern of the composite electrolyte, indicating that V2O5 was successfully retained and introduced into the polymer matrix during the composite process. The reduced intensity of the polymer characteristic peaks in the membrane proves that the filler effectively reduced the crystallinity of the polymer.

[0036] Example 2: The overall method is the same as in Example 1, except that the amount of each component added during the preparation of the polymer electrolyte membrane is as follows: succinate: 1.0 g, sodium bis(trifluoromethanesulfonyl)imide: 0.5 g, ethoxylated trimethylolpropane triacrylate: 0.5 g, fluoroethylene carbonate: 0.1 g, vanadium-based inorganic filler: 0.05 g, 2-hydroxy-2-methylphenylacetone: 0.005 g; a polymer electrolyte membrane (thickness approximately 830 micrometers) is obtained.

[0037] Example 3: The overall method is the same as in Example 1, except that the amount of each component added during the preparation of the polymer electrolyte membrane is as follows: succinate: 1.0 g, sodium bis(trifluoromethanesulfonyl)imide: 0.45 g, ethoxylated trimethylolpropane triacrylate: 0.4 g, fluoroethylene carbonate: 0.07 g, vanadium-based inorganic filler: 0.07 g, 2-hydroxy-2-methylphenylacetone: 0.007 g; a polymer electrolyte membrane (thickness approximately 970 micrometers) is obtained.

[0038] Example 4: Preparation of a solid-state sodium metal battery using the polymer electrolyte membrane obtained in Example 1, specifically including the following steps: (1) Preparation of positive electrode: Sodium vanadium phosphate, acetylene black and polyvinylidene fluoride are mixed and ground in a mass ratio of 7:2:1 and dispersed in N-methylpyrrolidone to form a film liquid; the film liquid is coated on aluminum foil (coating thickness is about 100 micrometers) and vacuum dried at 120°C for 12 hours to obtain sodium vanadium phosphate positive electrode (diameter 14 mm). (2) Battery assembly: In an argon glove box, the sodium metal anode (14 mm in diameter and 0.5 mm in thickness), the polymer electrolyte membrane prepared in Example 1, and the sodium vanadium phosphate cathode are stacked in sequence, placed in a CR2032 battery case, and packaged with a battery packaging machine to obtain a solid sodium metal battery.

[0039] Example 5: The overall method is the same as that in Example 4, except that in the process of preparing the vanadium-based inorganic filler containing oxygen vacancies in the raw material of the polymer electrolyte membrane, the material is calcined at 350°C for 1 hour.

[0040] Example 6: The overall method is the same as that in Example 4, except that in the process of preparing the vanadium-based inorganic filler containing oxygen vacancies in the raw material of the polymer electrolyte membrane, the material is calcined at 400°C for 1 hour.

[0041] Example 7: The overall method is the same as that in Example 4, except that in the process of preparing the vanadium-based inorganic filler containing oxygen vacancies in the raw material of the polymer electrolyte membrane, the material is calcined at 400°C for 2 hours.

[0042] Comparative Example 1: The overall method is the same as that of Example 4, except that no vanadium-based inorganic filler is added during the preparation of the polymer electrolyte membrane.

[0043] Performance testing and results analysis: The performance of the solid-state sodium metal batteries in Examples 4-7 and Comparative Example 1 was tested, and the results are as follows: 1. Electrochemical window testing The solid-state sodium metal batteries of Examples 4-7 and Comparative Example 1 were tested using linear sweep voltammetry (LSV). The voltage window results are shown in [Figure number missing]. Figure 3 and Table 1: Table 1 Voltage windows for different electrolytes

[0044] from Figure 3As can be seen from Table 1, the voltage window of the electrolytes prepared in Examples 4-7 is significantly widened to above 5.0V, while the voltage window of the electrolyte prepared in Comparative Example 1 without vanadium-based inorganic fillers is only 4.7V. Among them, the voltage window of the electrolyte prepared in Example 4 is significantly widened to 5.5V, which can be matched with high-voltage cathode materials, proving that vanadium-based inorganic fillers containing oxygen vacancies can effectively improve the oxidation stability of electrolytes.

[0045] 2. Room temperature ionic conductivity test The solid sodium metal batteries of Examples 4-7 and Comparative Example 1 were subjected to bulk impedance R tests using the electrochemical impedance spectroscopy (EIS). The ionic conductivity was calculated using the formula σ = L / (R × S) (where σ is the ionic conductivity, L is the film thickness, and S is the steel sheet area). The measured and calculated ionic conductivity results are shown in [the table / document / reference]. Figure 4 and Table 2: Table 2. Room temperature ionic conductivity of different electrolytes

[0046] from Figure 4 As shown in Table 2, the room-temperature ionic conductivity of the electrolytes prepared in Examples 4-7 is higher than that of Comparative Example 1; among them, the room-temperature ionic conductivity of Examples 4 and 5 reaches 2.98 mS / cm and 3.13 mS / cm, respectively, which is much higher than that of Comparative Example 1 (1.58 mS / cm), proving that the vanadium-based inorganic filler in this invention can effectively accelerate the Na+ process. + transmission.

[0047] 3. Sodium ion transfer number test The sodium ion transfer numbers of the solid sodium metal batteries in Example 4 and Comparative Example 1 were tested using the chronoamperometry (CA) method. The results of the sodium ion transfer numbers are shown in [the table below]. Figure 5 , 6 : from Figure 5 As can be seen, the sodium ion transfer number in the solid-state sodium metal battery of Comparative Example 1 is 0.288; from Figure 6 As can be seen, the sodium ion transfer number in the solid sodium metal battery of Example 4 is 0.322; the results show that the oxygen vacancies of the vanadium-based inorganic filler can anchor TFSI⁻ anions, reduce anion migration, thereby increasing the sodium ion transfer number and reducing concentration polarization.

[0048] 4. Critical Current Density Test The critical current density of the solid sodium metal battery in Example 4 and Comparative Example 1 was tested by gradually increasing the current density. The results of the critical current density test are shown in Figure 7. In Example 4, the critical current density of the solid sodium metal battery was 2.6 mA / cm². 2The critical current density of the solid sodium metal battery in Comparative Example 1 is approximately 1.3 mA / cm². 2 The results show that the electrolyte of the solid sodium metal battery in Example 4 can withstand higher current density and has better high-power discharge potential.

[0049] 5. Long-cycle stability test The cycle performance of the solid sodium metal batteries of Example 4 and Comparative Example 1 was tested at a 0.5C rate, and the results are shown in [Figure Number]. Figure 8 , 9 : The solid sodium metal battery in Example 4 maintained a capacity retention of over 98% after 200 cycles, and its polarization voltage remained stable. In contrast, the solid sodium metal battery in Comparative Example 1 began to show significant capacity decay after 100 cycles, and its capacity retention was less than 80% after 200 cycles. The results indicate that vanadium-based inorganic fillers can stabilize the electrode-electrolyte interface and inhibit sodium dendrite growth, thereby improving the long-cycle stability of the battery.

[0050] The above are preferred embodiments of the present invention. For those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler, characterized in that, It includes the following steps: (1) Preparation of deep eutectic solution: Mix succinate and sodium salt in a mass ratio of 2-2.5:1 to obtain a clear and transparent deep eutectic solution; (2) Mixing: The deep eutectic solution in step (1) is mixed with ethoxylated trimethylolpropane triacrylate and fluoroethylene carbonate in a mass ratio of 1:0.3-0.5:0.05-0.1 to obtain a mixed solution; (3) Preparation of precursor solution: The mixture in step (2) is mixed with vanadium-based inorganic filler at a mass ratio of 1:0.05-0.1 to form a precursor solution; (4) Preparation of polymer electrolyte membrane: The precursor solution and initiator in step (3) are mixed evenly at a mass ratio of 1:0.005-0.01, and then dropped onto the glass fiber membrane to completely wet the glass fiber membrane. Then, the membrane is irradiated with an ultraviolet lamp for 10-30 min to obtain the polymer electrolyte membrane.

2. The method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler according to claim 1, characterized in that, The sodium salt in step (1) is sodium bis(trifluoromethanesulfonyl)imide.

3. The method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler according to claim 1, characterized in that, The preparation method of the vanadium-based inorganic filler in step (3) includes the following steps: placing vanadium pentoxide powder in a reducing gas and calcining it at a temperature of 350-400℃ for 1-2 hours to obtain vanadium-based inorganic filler containing oxygen vacancies.

4. The method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler according to claim 3, characterized in that, The reducing gas is a hydrogen-argon mixture, wherein hydrogen accounts for 3-5% of the mass of the hydrogen-argon mixture.

5. The method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler according to claim 1, characterized in that, The initiator in step (4) is 2-hydroxy-2-methylacetone.

6. The method for preparing a polymer electrolyte with oxygen-vacancy vanadium-based filler according to claim 1, characterized in that, Steps (1)-(4) are carried out under an argon protective atmosphere.

7. A polymer electrolyte with oxygen-vacancy vanadium-based filler, characterized in that, The polymer electrolyte membrane is prepared by the preparation method described in any one of claims 1-5.

8. The polymer electrolyte with oxygen-vacancy vanadium-based filler according to claim 7, characterized in that, The thickness of the polymer electrolyte membrane is 800-980 μm.

9. The application of the polymer electrolyte with oxygen-vacancy vanadium-based filler as described in claim 8 in a solid-state sodium metal battery.

Citation Information

Patent Citations

  • Preparation method of lithium metal battery based on two-dimensional inorganic filler polymer electrolyte

    CN120511369A

  • Magnesium-based hydrogen storage material taking oxygen vacancy-rich vanadium pentoxide as catalyst and preparation method of magnesium-based hydrogen storage material

    CN116143069A

  • Preparation method and application of composite plastic crystal electrolyte with molecular brush

    CN117936892A

  • Composite solid electrolyte as well as preparation method and application thereof

    CN118173864A

  • Composite ionic conducting electrolytes

    US20130026409A1